SCIENTIFIC HERITAGE OF MIRZO ULUGBEK - Musalim Nuriddinov (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. In the history of the Middle Ages, Mirzo Uligbek's scientific legacy was of great service to the Renaissance. It is natural that the study of this process contributes to the development of world science.